Nests, arcs and cycles in the lifespan of a studio project. Issue 1 (19th December 2014) - Slater, Mark
Abstract Middlewood Sessions produced a kind of popular music that infuses the timbral aesthetics of jazz and orchestral music with the driving rhythms of dance music. This studio project, lasting for almost eight years, provided a rich resource for gaining insight into the increasingly prevalent context of the domestic project studio via a longitudinal case study approach. At the heart of this research is the desire to understand how people collaborate as part of a studio project, how people use technologies to make music and how all of this unfolds over time. To tackle the question of how to understand the shattered, scattered nature of creative practices, and in extending existing creativity research, I propose three ways of thinking about time: nests, arcs and cycles. While explicating this theoretical framework, something of the specific and idiographic nature of the case study, as an example of contemporary music production, is recounted.